ORGANIZATIONAL TRANSFORMATIONAL INITIATIVE: HOW ORGANIZATIONAL TRANSFORMATION IN TELECOM SECTOR ALONG WITH OPERATING MODEL & NEW ORGANIZATIONAL BLUEPRINT HELPS TO ACHIEVE THE REQUIRED CHANGE - Choudhury, Saumya; Singh, Pavitar Parkash (International Journal of Psychosocial Rehabilitation, 2020)
The telecommunication sector around the world has gone through the dramatic changes since 1980 due to various technological advancement and consumers now understand this as both product and services. Apart from voice and SMS, it has also a wide range of products like mobile money, virtual payment, digital commerce, over the top (OTT) social networking applications, virtual credit card, live video streaming, etc. The new 5G implementations will bring faster data ingestion and the streaming data flow will contribute to huge data growth by 2020. The Telecom Cloud adoption will help companies to stay connected to the world with minimal hardware cost. Also, nowadays almost similar price plans are offered by the telecom service providers and as a result, it cannot be the only differentiator when ARPU is declining and subscriber growth is slowing down.